Molecular Simulations of Porous Solids for Adsorption Applications - Glover, Joseph (2021)
The separation of gaseous mixtures plays a significant role across environmental, commercial, medicinal and analytical applications. In recent years, the emergence of metal-organic and covalent-organic frameworks has created a lot of attention within the material science community due to the versatile and highly tunable range of attractive physical and chemical properties that they possess. Due to the exceptionally large design space of these materials, it is often infeasible to synthesise and test each new material. Therefore, the viability of these materials for gas storage and separation applications is often predicted from computational modelling tools that can accurately characterise and assess the performance from molecular models of the adsorbent and adsorbates. In this thesis, different computational tool kits are employed to accurately characterise the structural properties of these materials and design a high-throughput protocol that can efficiently screen thousands of materials for membrane-based separations. The results may ultimately help the future design of novel membranes by providing relationships between the best performing materials and their structural design.